2007
DOI: 10.7863/jum.2007.26.12.1761
|View full text |Cite
|
Sign up to set email alerts
|

Primary Thyroid Lymphoma

Abstract: Our results show that ultrasound-guided core needle biopsy can be a safe and accurate method for diagnosing thyroid lymphoma and may be a suitable replacement for diagnostic thyroid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In addition, several studies showed that CNB could be a useful next-management tool for thyroid nodules with previously atypia (follicular lesion) of undetermined significance in FNA (18193839). When thyroid lymphoma or anaplastic cancer is suggested, CNB is preferable to FNA in many studies (16404142). A recent study suggested a role for CNB in medullary thyroid carcinoma (43).…”
Section: Indicationsmentioning
confidence: 99%
“…In addition, several studies showed that CNB could be a useful next-management tool for thyroid nodules with previously atypia (follicular lesion) of undetermined significance in FNA (18193839). When thyroid lymphoma or anaplastic cancer is suggested, CNB is preferable to FNA in many studies (16404142). A recent study suggested a role for CNB in medullary thyroid carcinoma (43).…”
Section: Indicationsmentioning
confidence: 99%
“…In this case, with a rapidly expanding thyroid mass causing airway compromise, there were two malignant differentials to consider—lymphoma and anaplastic thyroid carcinoma. The CT scan showed necrosis and, although a differential was not given in the report, this is more frequently associated with anaplastic carcinoma than lymphoma 1 …”
Section: Discussionmentioning
confidence: 69%
“…The CT scan showed necrosis and, although a differential was not given in the report, this is more frequently associated with anaplastic carcinoma than lymphoma. 1 Anaplastic carcinoma and lymphoma can be differentiated on cytology as in anaplastic carcinoma the cells may be epithelioid, spindled, rhabdoid, or form multinucleate giant cells and the nuclei are highly irregular. 2 In contrast, the MGG and PAP stains in this case, shown in Figures 1 and 2, respectively, show large monotonous atypical lymphoid cells.…”
Section: Discussionmentioning
confidence: 99%
“…He does not exhibit any other symptoms consistent with a lymphoproliferative disorder and the FNA cytopathology also rules out this diagnosis. A primary thyroid lymphoma is a rare cancer and could be eliminated as a possibility through biopsy cytopathology and additional immunocytochemical staining if needed (Kwak et al, 2007).…”
Section: Explanation Of Incorrect Answersmentioning
confidence: 99%